2021
DOI: 10.1038/s41598-021-97532-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of Plasmodium vivax malaria by the rotating-crystal magneto-optical method in Thailand

Abstract: The rotating-crystal magneto-optical detection (RMOD) method has been developed for the rapid and quantitative diagnosis of malaria and tested systematically on various malaria infection models. Very recently, an extended field trial in a high-transmission region of Papua New Guinea demonstrated its great potential for detecting malaria infections, in particular Plasmodium vivax. In the present small-scale field test, carried out in a low-transmission area of Thailand, RMOD confirmed malaria in all samples fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Furthermore, RDTs do not indicate parasite burden and may face detection problems when the parasite does not express the target antigen [13,14]. Due to the intrinsic limitations of conventional malaria diagnostic methods and the challenges faced by countries approaching elimination, a large number of new diagnostic methods have been proposed [15][16][17][18][19][20][21][22]. The most sensitive methods (around five parasites/µL of blood) are those based on DNA amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RDTs do not indicate parasite burden and may face detection problems when the parasite does not express the target antigen [13,14]. Due to the intrinsic limitations of conventional malaria diagnostic methods and the challenges faced by countries approaching elimination, a large number of new diagnostic methods have been proposed [15][16][17][18][19][20][21][22]. The most sensitive methods (around five parasites/µL of blood) are those based on DNA amplification.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been described previously, the anisotropic magnetic and optical properties of HZ can be utilized for its simple, yet highly sensitive detection and quantification in samples derived from cell cultures, animal models and malaria patients 5 , 19 , 20 . The quantification of HZ in blood samples of suspected malaria patients has the benefit of providing a quantitative parameter that can aid the assessment of disease severity, in contrast to RDTs for example, which only give a qualitative diagnostic result.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been described previously, the anisotropic magnetic and optical properties of HZ can be utilized for its simple, yet highly sensitive detection and quanti cation in samples derived from cell cultures, animal models and malaria patients 5,19,20 . Furthermore, we have demonstrated that the rotating-crystal magneto-optical detection (RMOD) developed by our research group, is an e cient tool for the assessment of drug susceptibility of P. falciparum cell cultures via the quanti cation of their HZ production with high temporal resolution 21,22 .…”
Section: Introductionmentioning
confidence: 99%